Integration of BIM methodology into the transversal teaching of architecture - Aldeanueva-Fernández, Mercedes; García-Marín, Alberto; García-Granja, M. J.; Barrios-Corpa, Jorge (RU Books, 2018)
Given the need and the evident progress of the implementation of the BIM Methodology in the AEC sector in our country, it is necessary to transfer new forms of teaching to the academic field that prepare the student for this incipient reality. The strategy of a new teaching method and a multidirectional and integrationist work philosophy must be taken from the joint collaboration of the Schools of Architecture and Engineering and their respective departments. In the same way, it must be a descending pyramidal decision, that is, the management and teaching staff of the Schools must assume the need for change and help, to the best of their ability, to consolidate a high level of long-term BIM maturity in Spain. . With this objective, the creation of a BAP (BIM Academy Plan) is proposed: a document that maintains obvious similarities with the BEP (BIM Executive Plan), and that allows the customization of the different study plans through the regularization and standardization of the different parts. In this way, the possibility of order and the interoperability of all the parts is demonstrated without sacrificing the originality or the distinction of each one of the agents. The BIM Academy Plan (BAP) takes, for consistency, as a reference the regulations to which the Spanish commission es.BIM (BSSCHE) looks and is structured into three areas of action: 1. Management 2. Training 3. Scope or the BIM philosophy. In the following communication, each of the parts are explained, understood as essential in the short term to eliminate the duplication of roles that the sector suffers in the workplace and reduce the distance between the current training that students receive and the reality that is will find at the end of the studies.
Se adjunta archivo de autorización del editor del libro para la publicación del capítulo en RUIMA
Keywords: Arquitectura; Programas de estudio; BIM; BEP; Methodology; Teaching innovation; Academic Plan; Interoperability; School of Architecture; Malaga